Forced vibration analysis of sandwich plates with an auxetic honeycomb core and laminated composite three-phase skin layers resting on Kerr foundation - Le, Truong Son (Journal of Military Science and Technology, 2025)
This paper introduces isogeometric analysis (IGA) based on higher-order shear deformation theory (HSDT) for vibration analysis of sandwich plates resting on Kerr foundation (KF). The sandwich plates include the ultra-light of an auxetic honeycomb core layer and are reinforced by two laminated composite three-phase skin layers. The governing equation is derived from Hamilton's principle. The Newmark-β method is applied to solve the forced vibration of the sandwich plates by the code in Matlab software. The accuracy of the proposed method is verified through comparative examples. Additionally, the effects of geometrical dimensions, material properties, and foundation stiffness on the forced vibration of sandwich plates are studied in detail.